Comparative Study of 10 Wp Solar Panel Performance with Mirror Reflectors at Various Angles - BASYARUDDIN ISMAIL HARAHAP; SEPTIA REFLY; DOLI BONARDO; BAVITRA BAVITRA; BIMBI ADYTIA WANATIRTA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Improving solar panel performance is challenging due to increasing of solar radiation. This study investigates the effect of variations in the angle of the flat mirror reflector on the surface temperature and electrical performance of a 10 Wp monocrystalline solar panel using an ESP32-based data acquisition system with INA219 and DS18B20 sensors. Reflector angles of 45°, 60°, and 75° were tested from 08:00 to 16:00 WIB. The results indicate that the 45° reflector produced the lowest temperature (≈60 °C), the highest average voltage (19.7–20.0 V), maximum current of 120 mA, and peak power of 2.6 W. In contrast, the 75° angle increased the temperature to 72 °C and reduced the electrical output. The study concludes that a 45° reflector angle is optimal for low-power solar panels in hot tropical environments.